Stability analysis for yield and yield components through AMMI and GGE biplot techniques in germplasm of finger millet (Eleusine coracana) - MANNA, PRATIK; SWAPNIL; ROUT, SANGHAMITRA; RASHMI, KUMARI; SAHAY, SANJAY; SUSMITHA, PUSARLA; SINGH, DIGVIJAY (The Indian Journal of Agricultural Sciences, 2026)
An experiment was conducted during the winter (rabi) season of 2022–23 and 2023–24 to evaluate the stability and adaptability of 35 diverse finger millet (Eleusine coracana L. Gaertn.) germplasm across three environments, namely Odisha (E1), Bihar (E2), and West Bengal (E3). The experiment was laid out in a randomised complete block design (RCBD) with three replications. Data on 15 quantitative traits were recorded to assess genotype × environment (G × E) interactions using AMMI and GGE biplot models. AMMI analysis revealed significant G × E interactions for key traits such as biological yield/plant, harvest index and grain yield/plant, indicating differential genotype responses across environments. GGE biplot analysis showed that the first two principal components (PC1 and PC2) explained 91.05% of the total yield variation, effectively capturing genotype performance and stability. E1 (Odisha) emerged as the most discriminative environment, while E2 (Bihar) was both discriminative and representative, making it suitable for selecting widely adaptable genotypes. Genotypes Badatara, FM 1213, Chillika and FM PR 1731 exhibited stable and superior yield performance across environments. The “which-won-where” biplot identified VL 410, Badatara and FM 1213 as top performers in Odisha, Bihar and West Bengal, respectively. Positive associations among environments, inferred from acute angles between environment vectors in the GGE biplot, indicated consistent genotype performance across locations. Overall, the study demonstrated that both AMMI and GGE biplot approaches are effective for selecting high-yielding and stable finger millet genotypes.